The European Security and Defense Policy : NATO's companion - or competitor? - Hunter, Robert Edwards, 1940- (RAND, 2002)
The European Union's new European Security and Defense Policy is a major step toward full European integration, in parallel with progress toward a Common Foreign and Security Policy. This work tells the story of ESDP's relationship to NATO.